Réponses

2013-02-25T17:25:48+01:00

 

(3x - 7)² < (5x + 3)²

(3x - 7)² - (5x + 3)² < 0

(3x-7 - 5x - 3)(3x-7+ 5x+ 3) < 0

(-2x-10)(8x-4)<0 je suppose que tu as vu le signe de la fonction du 2d d°.

 

x             -5                       1/2

f(x)     -     0            +           0          -          solution: -infini; -5[ ou ]1/2; infini

 

3x-1/5x >=1/x

(3x-1)/5x - 1/x >=0

(15x - 5 -1)/5x >=0

(15x - 6 ) / 5x  >=0

x        0                  2/5

f(x)  + |       -            0       + solution -infini; 0[ ou [2/5; infini